Dynamic resistance signal–based wear monitoring of resistance spot welding electrodes; International Journal of Advanced Manufacturing Technology; Vol. 133 - Dawei Zhao; Vdonin N. Nikita; Slobodyan M. S. Mikhail Stepanovich; Butsykin S. E. Sergey Eduardovich; Kiselev A. S. Aleksey Sergeevich; Gordynets A. S. Anton Sergeevich; Wang Yuanxun (2024, 2024)
Title screen